2022
DOI: 10.1590/fst.43722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maillard reaction browning factors on color of membrane clarification non-centrifugal cane sugar during storage

Abstract: The effect of Maillard reaction browning factors on the color enhancement of membrane clarification non-centrifugal cane sugar (M-NCS) in storage was explored. During storage, the color of M-NCS gradually browned and blackened. pH, the contents of glucose, fructose, protein, total amino acids and 5-hydroxymethylfurfural (5-HMF) decreased significantly. Meanwhile, the moisture content, relative percentages of volatile Maillard reaction products (MRPs) and the content of 3-deoxyglucosone (3-DG) increased during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The addition of several effective additives can increase the TS content in tobacco leaves, but has no significant effect on RS content. At the end of fermentation process, RS is almost completely consumed by biochemical reaction, such as Maillard reaction and caramel reaction (Chen et al, 2022;. Therefore, adding amylase could improve the sweetness of tobacco leaf remarkably, which was consistent with the results of sensory quality evaluation.…”
Section: Major Chemical Compositions Analysissupporting
confidence: 79%
“…The addition of several effective additives can increase the TS content in tobacco leaves, but has no significant effect on RS content. At the end of fermentation process, RS is almost completely consumed by biochemical reaction, such as Maillard reaction and caramel reaction (Chen et al, 2022;. Therefore, adding amylase could improve the sweetness of tobacco leaf remarkably, which was consistent with the results of sensory quality evaluation.…”
Section: Major Chemical Compositions Analysissupporting
confidence: 79%
“…The change in color caused by convective drying is explained by two phenomena: Maillard reactions and enzymatic browning. The Maillard reaction is a reaction occurring between amino groups of free amino acids, peptides, or proteins and reducing sugars [46,47]. Products of this reaction are known as Amadori products-compounds with a brown color and a characteristic smell of roasted meat, but which are impossible to describe with a chemical formula due to their diversity caused by the variety of substrates in a given environment [48].…”
Section: Statistical Analysis By Mechanical Texture Color Rgb Color L...mentioning
confidence: 99%
“…This could also explain well why the taste evaluators provided a higher score for bitterness attributes. In addition, the Maillard reaction also causes bitter taste during high-temperature sterilization of sugarcane juice (Chen et al, 2022). Recent studies have shown that bitter beverages can give a sense of bitterness when consumed, leading to an endless aftertaste for bitter flavors, such as coffee, tea, grapefruit juice (Zhong et al, 2019).…”
Section: Sensory Evaluation Of Beveragementioning
confidence: 99%